Electrical conductivity test to differentiation of deteriorating levels of forage seeds - Pinto, Adriana Hernandes; Silva Binotti, Flavio Ferreira da; Souza, Hugo Manoel; Batista, Thiago Barbosa [UNESP]; Cabral Gouveia, Geraldo Candido (Univ Estadual Mato Grosso Sul, 2016)
The electrical conductivity test stands out for generating rapid responses to differentiation of seed lots at different deterioration levels. However, there is need for further studies to improve this practice for forage species such as Brachiaria brizantha and Panicum maximum. The objective was to adjust the electrical conductivity test to differentiation of deterioration level of B. brizantha seeds MG-5 and P. maximum cv. Tanzania. The experimental design was completely randomized and the treatments arranged in a factorial 3 x 3, three levels of deterioration and three soaking periods (8, 16 and 24 hours) at 25 degrees C with 6 repetitions. The electrical conductivity in three water volumes of imbibition solution (25, 50 and 75 mL) and three amounts of seeds (25, 50, and 75 seeds) were measured. It is recommended to Brachiaria brizantha cv. MG-5 using 25 seeds within 8 hours on electrical conductivity, regardless of the amount of soaking solution. For Panicum maximum cv. Tanzania using 50 seeds in 25 ml of soaking solution independent of the soaking period is appropriate.
Keywords: soaking period; Brachiaria brizantha; Panicum maximum; force; physiological quality